2005
DOI: 10.1111/j.1365-2273.2004.00947.x
|View full text |Cite
|
Sign up to set email alerts
|

A multivariate analysis of otological, surgical and patient‐related factors in determining success in myringoplasty

Abstract: A non-smoking patient, a longer dry ear, a healthy opposite ear, a relatively smaller perforation and a senior surgeon were found to be significant prognostic factors positively influencing the success rate of myringoplasty.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
139
2
9

Year Published

2011
2011
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 175 publications
(160 citation statements)
references
References 20 publications
9
139
2
9
Order By: Relevance
“…They recommended that ears with initial discharge should be medically treated and that tympanoplasty should be performed after a 3-month period without any ear discharge. Although some authors have reported that preoperative otorrhea did not affect tympanoplasty success, tympanoplasty was performed following a non-discharge period of at least 3 months, particularly in children [23,24,28] . If there is a hypertrophic adenoid tissue that requires surgery, first, adenoidectomy is performed, and then, tympanoplasty is performed in the following months.…”
Section: Discussionmentioning
confidence: 99%
“…They recommended that ears with initial discharge should be medically treated and that tympanoplasty should be performed after a 3-month period without any ear discharge. Although some authors have reported that preoperative otorrhea did not affect tympanoplasty success, tympanoplasty was performed following a non-discharge period of at least 3 months, particularly in children [23,24,28] . If there is a hypertrophic adenoid tissue that requires surgery, first, adenoidectomy is performed, and then, tympanoplasty is performed in the following months.…”
Section: Discussionmentioning
confidence: 99%
“…By the 1980s, most otologists were convinced that a graft of mesodermal origin, such as perichondrium, fascia, vein, or fat tissue, was advantageous in myringoplasty [9] . Several factors may affect the outcome of myringoplasty, such as the site and size of the perforation, technique (underlay versus overlay), approach (endaural versus postaural), experience of the surgeon, condition of the other ear, type of used graft, age of the patient, and condition of the operated ear (dry versus wet) [5,[10][11][12][13][14] .…”
Section: Introductionmentioning
confidence: 99%
“…A healthy mucosa lining the middle ear cleft can be achieved after a successful tympanoplasty. [3] Graft success is an important component after tympanoplasty because it prevents recurrent middle ear infections and may…”
Section: Discussionmentioning
confidence: 99%
“…Tobacco smoking, pathology in the opposite ear, the size of the tympanic membrane perforation, experience of the surgeon, and duration of the dry period have been reported as prognostic factors for success after tympanoplasty. [3] Other factors suggested to be associated with the surgical outcome of tympanoplasty are age, sex, perforation size and site, ear status at the time of surgery, and surgeon experience; however, the actual roles of these factors remain controversial. [4,5] Graft success is an important occurrence after tympanoplasty.…”
mentioning
confidence: 99%